STUDI KELAYAKAN FINANSIAL USAHA KERUPUK IKAN LAUT DI DESA JATIREJO KECAMATAN TIKUNG KABUPATEN LAMONGAN - Sa'adah, Wachidatus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Fish is a source of animal protein that is needed by humans, has a high protein content compared to other animal protein sources, but has the disadvantage of quickly decomposing. Seeing these conditions, it is necessary to handle and process fishery products, so as to increase the durability and diversify fish processing products. The handling and processing methods applied include the method of making fish crackers. The purpose of this study was to determine the feasibility of the marine fish cracker business in Jatisari Village, Lamongan District, Lamongan Regency. The research method uses a quantitative approach. The annual income is IDR 57,600,000, the profit per year is IDR 21,155,000, then the R/C Ratio is 1.58, and the sales BEP is IDR 2,388,038, and the BEP unit is 398